Linalool-Linalyl Acetate as a Non-steroidal Alternative to Mometasone-Salicylic Acid Therapy in Imiquimod-induced Psoriasis Model - Debasish Sahoo; Vipin Kumar Singh; Km. Sushmita; Debabrata Chanda; Narayan Prasad Yadav (Journal of Pharmaceutical Innovation, 2026)

Genomic and transcriptomic characterization of genes expressed at 20 MPa by the marine actinobacterium Kocuria flava - A. Ganesh Kumar; K. Sujitha; D. Sushmita Dubey; D. Magesh Peter; G. Dharani; Balaji Ramakrishnan (Marine Pollution Bulletin, 2026)

Hydrocarbons and genomic biomarker-based paleoclimate and ecological variability over the past 15 kyr from Toli Lake, Garhwal Himalaya - Sushmita Singh; Vishakha Bisht; Ambili Anoop; Shravi Agarwal; Pankaj Kumar; A.S. Maurya; Naveen K. Navani; A.P. Dimri; Pradeep Srivastava (Quaternary Science Reviews, 2026)

Retraction Note: Adipose tissue derived mesenchymal stem cells are better respondents to TGFβ1 for in vitro generation of cardiomyocyte‑like cells - Anupama Kakkar; Sushmita Bose Nandy; Suchi Gupta; Balram Bharagava; Balram Airan; Sujata Mohanty (Molecular and Cellular Biochemistry, 2026)

Greenhouse gas emissions: trends, impacts, and global mitigation approaches - Sushmita; Amandeep Kaur; Amanpreet Kaur; Pawan Kumar (Arabian Journal of Geosciences, 2026)

Transitional hypoxia during peatland water table fluctuations drives high N2O fluxes via shifting microbial pathways - Mohit Masta; Fahad Ali Kazmi; Mikk Espenberg; Triinu Visnapuu; Louise B. Sennett; Lauri Eving; Dominika Lewicka-Szczebak; Sushmita Deb; Ramita Khanongnuch; Laura Kuusemets; Priit Kupper; Klaus Butterbach-Bahl; et al. (Environmental Research, 2026)

A multi-ingredient food supplement slows age-dependent decline of mobility and influences gene expression in C. elegans - Chad Yanyatan; Karthik Mohanraj; Michael Fasseas; Sushmita Maitra; Ed Van Harmelen; Chris Saunter; David Weinkove (Biogerontology, 2026)
The goal of developing interventions to slow ageing is not only lifespan extension but more importantly to increase healthspan, the period of life spent in active good health. Nutritional interventions have emerged as a potential strategy to maintain health with age. Testing these interventions for effects on human ageing would take several years and require large cohort sizes. We therefore employed C. elegans as a rapidly ageing model organism to investigate the effects of two commercially available nutrition-based products on ageing-related decline of mobility as an indication of healthspan. These products are multi-ingredient formulations comprising vitamins, minerals, antioxidants, amino acids and botanical extracts. They include compounds expected to positively influence ageing such as Dihydronicotinamide mononucleotide, NAD + booster, trans-resveratrol, taurine, pterostilbene and bioflavonoids. V14™ contains 40 + ingredients and AG1® contains 70 + ingredients with 5 additional probiotic strains. Mobility-based readouts over time were obtained using WormGazer™ imaging technology. Worms exposed to V14™ showed increased movement and speed with age compared to those exposed to AG1® and to a solvent control. To investigate the underlying mechanisms, transcriptomic profiling was performed on V14™ exposed worms, revealing modulation of pathways involved in metabolism and stress responses, processes associated with ageing. Collectively, these findings suggest that V14™ delays age-related decline in C. elegans and highlight the potential of targeted nutritional interventions to modulate pathways relevant to human ageing.

Harmonizing plant defenses: exploring phytohormones, and their interplay in biotic stress responses - Baisista Saha; Jagatjeet Nayak; Sushmita Saha; Nidhi Singh; Mrunmay Kumar Giri (Acta Physiologiae Plantarum, 2026)

Antifungal potential of B. amyloliquefaciens NBRI-SN13 against R. solani: Parallels and contrast with epigenetic modifier - Ananya Dwivedi; Akshita Maheshwari; Garima Saxena; Sushree Pallavi; Anamika Asthana; Sushmita; Babita Kumari; Mehar H. Asif; Suchi Srivastava (Process Safety and Environmental Protection, 2026)

The antidiabetic potential of Leuconostoc mesenteroides strain SB1075 fermented soy yoghurt: Insights from mouse intestinal transcriptomics and metabolite analyses - Maloyjo Joyraj Bhattacharjee; Yunus Sheikh; Sushmita Das; Asis Bala; Ashis K. Mukherjee; Mojibur Rohman Khan (Food Research International, 2026)

Quantification and characterization of soil organic carbon with different environmental gradients for the high altitude wetlands of Indian Himalaya - Narayan P. Anugraha; D. Ganguly; A. Paneer Selvam; Kakolee Banerjee; M. Harikrishna Prasad; Lakpa Tamang; Sushmita Chettri; Anupriya Soni; Rajesh Joshi; Ajay Kumar Gupta; Prakash Chhetri; Ramachandran Purvaja (Environmental Geochemistry and Health, 2026)

Spatio-hydrogeochemical assessment of groundwater in Saharsa, Bihar: Insight from HH-WQI and multivariate statistics - Sushmita Kumari; Somnath Mandal; Subrata Haldar; Amandeep Singh; Rajesh Jolly; Suman Paul; Sajad Nabi Dar (Environmental Monitoring and Assessment, 2026)

Precision nutrient management coupled with integrated weed control reduces weed pressure, enhancing the productivity, profitability and energy use indices of upland direct seeded rice - Smruti Ranjan Padhan; Sanjay Singh Rathore; Kapila Shekhawat; Shiv Mangal Prasad; Sushmita Saini; Subhash Babu; Soumya Ranjan Padhan; Shubham Anil Durgude (Field Crops Research, 2026)

Simultaneous removal of imidacloprid, carbendazim, and bispyribac sodium using zinc and bentonite functionalized rice husk biochar composite - Bibhab Mahapatra; Abhijit Kar; Arpita Pattanaik; Rakesh Ranjan Nayak; Arabinda Mahanty; Rubina Khanam; Sushmita Munda; Elssa Pandit; Pratap Bhattacharyya; Shyamaranjan Das Mohapatra; Totan Adak (Waste Management, 2026)

Biomass derived catalyst for valorization of waste glycerol to glycerol carbonate: Process optimization via response surface methodology - Sushmita Das; Bishwajit Changmai (Biocatalysis and Agricultural Biotechnology, 2026)

Development and Standardisation of a Digital Competency Index for Extension Professionals of India: A Principal Component Analysis Approach - Sweety Mukherjee; R. N. Padaria; R. R. Burman; Vinayak R. Nikam; Praveen Koovalamkadu Velayudhan; Girijesh Singh Mahra; Kaustav Aditya; Bidisha Chakrabarti; Sushmita Saini; Kotha Shravani; Bhaskar Ghosh (Agricultural Research, 2026)

HPLC evaluation of storage and Trichoderma treatment effects on major flavonoids in Oroxylum indicum seeds - Sushmita Uniyal; Sushil Bhattarai; A. N. Singh; Amit Pandey (Natural Product Research, 2026)

Berberine as a therapeutic alkaloid against ESKAPE and multiple drug-resistant bacteria: a comprehensive review - Sushmita Saha; Arpita Roy; Harjot Singh Gill; Mithul Rajeev; Moupriya Nag; Soumya Pandit; Dibyajit Lahiri; Debasmita Bhattacharya; Debapriya Maitra (Archives of Microbiology, 2026)

Integrative bacterial-metabolite compositional profiling of traditional fermented fish paste (Napham) reveals a core bacterial consortium for differential synthesis of fermentation-derived functional metabolites - Sushmita Das; Puja Sarma Phukan; Dimpi Kalita (Antonie van Leeuwenhoek, 2026)

Insecticidal and Repellent Effects of Selected Botanicals against Tribolium Castaneum (Herbst) (Coleoptera: Tenebrionidae) with Reference To their Effect on Detoxifying Enzymes - Awaneesh Kumar; Anjumoni Devee; Sushmita Thokchom; Abhinandan Yadav; Jehan Zeb; Mohammed E. Gad; Abdelfattah Selim; Hattan S. Gattan; Mohammed H. Alruhaili; Mohamed M. Baz; Haytham Senbill (Acta Parasitologica, 2026)

AI/ML-based computational models for toxicity prediction - Sushmita Barua; Badhrinarayanan Balaji; Seetharaman Balaji (Environmental Science and Pollution Research, 2026)
The increasing demand for accurate toxicity assessment and to minimise or eliminate the use of animal testing has accelerated the development of numerous computational models, AI/ML models, and online resources that support research in computational toxicology. This review addresses toxicity prediction and chemical safety evaluation, focusing on computational models and data coverage, Molecular Descriptors, QSAR models, AI/ML-based approaches, Explainable AI, predictive methodologies, regulatory relevance, and accessibility. This collectively enables the identification, prediction, and analysis of chemical toxicity across various biological endpoints. In addition, the review highlights AI/ML tools for predicting toxicity endpoints, such as neurotoxicity, hepatotoxicity, cardiotoxicity, genotoxicity, and environmental toxicity. Regulatory limitations vary significantly among countries and jurisdictions, exhibiting a marked absence of convergence. Current debates regarding regulatory norms focus on achieving global conformity. Regulatory adaptability is the key as AI evolves rapidly. The promotion of AI/ML tool integration and interoperable frameworks could substantially enhance the future of predictive toxicology.

Ficus deltoidea Preserves Hippocampal Neuronal Integrity and Redox Balance in Oxidative Stress-Driven Alzheimer’s Disease-Like Rat Model - Alhaji Modu Bukar; Che Mohd Nasril Che Mohd Nassir; Michael Ayuba; Sushmita Devi Manoharan; Abdulhamid Sani Usman; Babagana Isa Umar; Zaw Myo Hein; Mohamad Aris Mohd Moklas; Muhammad Zulfadli Mehat; Hafizah Abdul Hamid (Molecular Neurobiology, 2026)

Assessing mechanisms of intrinsic vulnerability in sharks occupying different marine environments - Sushmita Mukherji; Colin Simpfendorfer; Natalie Dowling; Nils C. Krueck (Biodiversity and Conservation, 2026)
The status of many shark species worldwide is concerning due to a combination of their life-history traits and widespread exposure to threats, especially fishing. However, the intrinsic vulnerability of species differ given that life-history traits vary with environmental conditions. Here, we aim to assess the links between sharks’ reproductive strategy, maximum depth recorded, and environment occupied (shelf, deepwater and pelagic) to investigate the varying levels of intrinsic vulnerability of different shark species. We find that shelf habitats are dominated by placental viviparous species that rarely occupy other environments. In contrast, oviparous species are found in both shelf and deep-sea habitats but are absent from pelagic environments due to a lack of substrate for egg deposition. Importantly, oviparous species reveal a significantly lower maximum size, size at birth, size at maturity as well as continuous reproduction, all of which are indicators of relatively high productivity and thus lower intrinsic vulnerability. In comparison, placental viviparous species reveal a larger maximum size, size at birth, size at maturity as well as annual or biennial reproduction. These life-history traits are indicative of lower productivity and thus higher intrinsic vulnerability of this dominant species group in shelf habitats where fishing mortality is known to be high. In consequence, placental viviparous species reveal higher proportion of species listed as threatened (VU, EN, CR) in the International Union for Conservation of Nature (IUCN) Red List compared to oviparous species. However, threats to deep-sea oviparous as well as to aplacental and lecithotrophic viviparous species (which are also abundant in deeper waters) are likely to increase in future due to the expansion of fisheries into open ocean and deeper waters. Although key life-history traits of deep-sea oviparous shark species are indicative of relatively higher productivity, these species have evolved under lower levels of primary productivity and predation risk characteristic of deeper waters. Slower growth and low natural mortality in deep sea oviparous species mean that the risk of population depletion is still high when mortality levels are elevated. Therefore, these findings underscore the importance of adopting precautionary and proactive strategies for sharks inhabiting deep-water environments.

Multi-elemental analysis and risk evaluation of trace metals in coastal sediments of the northern Bay of Bengal using EDXRF - Abdullah Al Mahmud; Taspiya Hamid; Sushmita Hossain; Yeasmin N. Jolly; Shirin Akter; J. Kabir; K.M. Mamun; Ishrat Jahan Eva; Tasmira Hamid; Md. Refat Jahan Rakib (Next Research, 2025)

Optimized Agrobacterium-mediated CRISPR/Cas9 transformation in soybean through comparative evaluation of cotyledonary node and half-seed explants - Durgeshwari Prabhakar Gadpayale; J. Sushmita; Navita Bansal; Shalini Singh; Ch Prasanna Kumari; C. R. Nagesh; Ranjeet Ranjan Kumar; G. Rama Prashat; Shivani Nagar; Soham Ray; R. Dinesh Kumar; Arun Kumar; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2025)

Biology, demographic traits and predation rate of Cheilomenes sexmaculata (Fabricius) (Coleoptera: Coccinellidae) on peach leaf curl aphid, Brachycaudus helichrysi (Kaltenbach) (Hemiptera: Aphididae) - Aryan Bhandari; Chander Singh; Subhash Chander Verma; Prem Lal Sharma; Vishav Gaurav Singh Chandel; Rajeshwar Singh Chandel; Anshuman Semwal; Sushmita; Simran Sharma (Phytoparasitica, 2025)

Targeted lipidome analysis reveals nutritionally enhanced foxtail millet genotypes across diverse grain colours - Palakurthi Ramesh; Sushmita Seni; Roshan Kumar Singh; Ashutosh Pandey; Manoj Prasad (The Nucleus, 2025)

Fabrication of nZVI/rGO via an innovative thermal co-reduction method for enhanced PFAS removal through sequential adsorption and photocatalytic degradation - Sushmita Regmi; Md Sayeduzzaman Sarker; Austin K. Oglesby; Kaitlyn N. Banning; Elle E. Lanier; Chunjie Xia; Sonkorson Talukder Sabuj; Haoran Yang; Nafeesa Khan; Jia Liu (Journal of Hazardous Materials, 2025)

Genetic variability, association and diversity analysis of yield and yield-associated traits in mulberry (Morus spp.) genotypes - M. R. Bhavya; M. Y. Jagadamba; G. S. Arunakumar; B. V. Sushmita; B. N. Gnanesh; P. Sowbhagya; N. R. Nisarga; T. Sarkar; C. M. Babu; S. G. Doss (Trees, 2025)

Biology and life tables of the predatory mite (Neoseiulus longispinosus) on different developmental stages of the two-spotted spider mite (Tetranychus urticae) on carnation (Dianthus caryophyllus) cultivars - Pankaj Sharma; Vishav Gaurav Singh Chandel; Subhash Chander Verma; Prem Lal Sharma; Rajeshwar Singh Chandel; Nikita Chauhan; Chander Singh; Anshuman Semwal; Aryan Bhandari; Sushmita Goel; Simran Sharma; Shashank Kaundal (Experimental and Applied Acarology, 2025)

A metagenomic assessment of overburden dump of coal mine soil bacterial consortium from Jharkhand, India - Vineet Vishal; Pankhuri Thakur; Sweta Sushmita Tigga; Shalini Lal (Environmental Monitoring and Assessment, 2025)

A Green Synthesised B/nZVCu-M On–Off Fluorescence Sensor for Dopamine Detection and its Reusability - Dipanwita Basak; Sushmita Gajurel; Aseem Vashisht; Hemaprobha Saikia (Journal of Fluorescence, 2025)

In-silico insights into Terminalia citrina targeting OmpA: an approach to combat multidrug resistance in Acinetobacter baumannii - Romen Meitei Lourembam; Jobina Rajkumari; Arunkumar Singh Koijam; Sushmita Bhattacharya; Sulagna Basu; Sunil S. Thorat; Sarangthem Indira Devi (In Silico Pharmacology, 2025)

Effect of sustainable household cooking techniques on nutritional, textural properties, and quality characteristics of finger millet (Eleusine coracana) flour porridge - Sushmita Mandal; Suresh Kumar Kalakandan; Suman Thamburaj; Rajendran Palanivel (Cereal Research Communications, 2025)

LC-ESI-HRMS-Based Evaluation of Antioxidants as Additives to Inhibit Genotoxic Nitrosamine Formation in Metformin Hydrochloride Tablets - Aishwarya Dande; Nikhil Pallaprolu; Sangita Gadilohar; Sushmita Mishra; Rajkumar Malayandi; Subramanian Natesan; Abhishek Sahu; Murali Kumarasamy; Ravichandiran Velayutham; Ramalingam Peraman (AAPS PharmSciTech, 2025)

Molecular confirmation of a new mosquito record Aedes lineatopennis from Odisha along with a comprehensive update of mosquito (Diptera: Culicidae) fauna in India - Sushmita Swain; Gaurav Sharma; Surabhi Chittora; Devi Shankar Suman (Biologia, 2025)

Sustainable activated carbon derived from biomass of Borassus flabellifer: Unveiling their potential as electrode in supercapacitors for triazolium ionic liquid-based systems - Chaithanya Vijay; E.P. Abhijith; Sushmita Sushil; Anjitha Satheesh; Elango Kandasamy (Bioresource Technology, 2025)

How urbanization and terrain characteristics shape precipitation and temperature patterns in complex geographies: a case study of the Doon Valley - Sushmita Gouraha; Dhyan Singh Arya; Piyush Srivastava (Theoretical and Applied Climatology, 2025)

Soil carbon and nitrogen dynamics under conservation agriculture components for direct seeded rice-green gram system - Gayatri Patra; Dibyendu Chatterjee; Khitish Chandra Moharana; Bitish Kumar Nayak; Rahul Tripathi; Mohammad Shahid; Dipti Ranjan Pani; Saikat Ranjan Das; Bipin Bihari Panda; Sushmita Munda; Upendra Kumar; Abhijit Pradhan; et al. (Plant and Soil, 2025)

The Relationship Between GAPDH Gene Polymorphism and Risk of Acute Coronary Syndrome in South Indians with Type 2 Diabetes Mellitus - Sushmita Bora; Prashant Shankarrao Adole; Kolar Vishwanath Vinod; Ajith Ananthakrishna Pillai; Shaheer Ahmed (Biochemical Genetics, 2025)

Susceptibility status of Anopheles culicifacies and Anopheles fluviatilis mosquitoes against DDT and deltamethrin in a tribal malaria zone of India - Birat Raja Padhan; Prasanta Nanda; Ekamber Kariali; Sushmita Swain; Devi Shankar Suman (International Journal of Tropical Insect Science, 2025)

Integrating multivariate statistical techniques and geochemical indices for water quality assessment in pond ecosystems of Kirtipur Municipality, Kathmandu, Nepal - Mahesh Prasad Awasthi; Ramesh Raj Pant; Kiran Bishwakarma; Gaurav Kumar Raut; Ganga Paudel; Sushmita Kafle; Virendra Bahadur Singh (Sustainable Water Resources Management, 2025)

Tomato miR398 knockout disrupts ROS dynamics during stress conferring heat tolerance but hypersusceptibility to necrotroph infection - Shreya Chowdhury; Ananya Mukherjee; Raghuvir Singh; Sushmita Talukdar; Shrabani Basak; Rohit Das; Sayan Mal; Pallob Kundu (Plant Molecular Biology, 2025)

Impact of Biochar and Water Regimes on Arsenic Transfer and Uptake in Rice: Insights into Transporter Behaviour and Soil–Plant Dynamics - Rubina Khanam; Lipsa Tripathy; Parameswaran Chidambaranathan; Pedda Ghouse Peera Sheikh Kulsum; Jajati Mandal; Mohammad Shahid; Manish Debnath; Raj Kishore Sahoo; Sushmita Munda; Sanghamitra Samantray; Amaresh Kumar Nayak (Exposure and Health, 2025)

Salt stress alleviation in peanut through calcium supplementation - Anchal Singh; Sushmita Singh; Kiran K. Reddy; Anuj K. Singh; Kamal Krishna Pal; Rinku Dey; Eugenia P. Lal (Acta Physiologiae Plantarum, 2025)

Comparative Assessment of Different Rearing Diets on the Developmental and Reproductive Behaviour of Fall Armyworm, Spodoptera frugiperda (Lepidoptera: Noctuidae) - Sushmita Banra; Jaipal Singh Choudhary; Luaay Kahtan Khalaf; Bilal Ahamad Paray; Mohammad Khalid Al-Sadoon; Anand Kumar Thakur; Anita Kumari; Priti Kumari Oraon; Naiyar Naaz (Neotropical Entomology, 2025)

Predicting the potential distribution of three invasive insect pests (Tuta absoluta, Aleurodicus rugioperculatus and Phenacoccus manihoti) under future climate scenarios in India based on CMIP6 projections - Guru-Pirasanna-Pandi Govindharaj; Sujithra M; Subhash Kumar Sahu; Swagatika Sahoo; Sushmita Banra; Jaipal Singh Choudhary (Theoretical and Applied Climatology, 2025)

Pollution status of microplastics in the sediments of warm monomictic Dal lake, India: Abundance, composition, and risk assessment - Samreen Sajad; Bharat Kumar Allam; Abhijit Debnath; Pargin Bangotra; Sushmita Banerjee (Environmental Pollution, 2024)

Decoding Potato Power: A Global Forecast of Production with Machine Learning and State-of-the-Art Techniques - Shikha Yadav; Abdullah Mohammad Ghazi Al khatib; Bayan Mohamad Alshaib; Sushmita Ranjan; Binita Kumari; Naief Alabed Alkader; Pradeep Mishra; Promil Kapoor (Potato Research, 2024)

Human exposure to uranium through drinking water and its detrimental impact on the human body organs - Ansumali Ashish; Pargin Bangotra; Venus Dillu; Mukesh Prasad; Sushmita Banerjee; Rohit Mehra; Nand Lal Singh (Environmental Geochemistry and Health, 2024)

Combinations of bacterial probiotics and yeast postbiotics influence fat deposition and growth in the nematode C. elegans - Michael K. Fasseas; Sushmita Maitra; Maria Tintoré; Jordi Cuñé; Carlos de Lecea; David Weinkove (PharmaNutrition, 2024)

Integrating microbial electrochemical cell in anaerobic digestion of vegetable wastes to enhance biogas production - Jarina Joshi; Puja Bhatt; Pratap Kandel; Mamata Khadka; Sanoj Kathariya; Sushmita Thapa; Susmita Jha; Sunita Phaiju; Suman Bajracharya; Amar Prasad Yadav (Bioresource Technology Reports, 2024)

A review on phytochemical mediated synthesis of nanoparticles through fruits and vegetables extract and their potential applications - Sushmita Bhatt; Shweta Saraswat (Nanotechnology for Environmental Engineering, 2024)

Establishment of axenic culture from basidiospores of an ectomycorrhizal fungus Astraeus asiaticus and A. odoratus - Vineet Vishal; Sweta Sushmita Tigga; Pitchapa Thongsuwan; Pisit Thamvithayakorn; Nuttika Suwannasai; Cherdchai Phosri; Manoj Emanuel Hembrom; Geetanjali Singh; Shalini lal (Indian Phytopathology, 2024)

High mortality in free-ranging wild boars associated with African swine fever virus in India - K. G. Sai Balaji; M Karikalan; S Saravanan; S Mahajan; K Rajeshkumar; Mirza Vaseem; Sushmita Nautiyal; Athira Subash; Kirtika Sharma; Sanchay Kumar Biswas; Sukdeb Nandi; Abhijit M Pawde; et al. (Archives of Virology, 2024)

Selection of a multi-species starter culture for mustard seed fermentation to enhance polyunsaturated fatty acids and improve gastrointestinal health markers - Sushmita Das; Maloyjo Joyraj Bhattacharjee; Ashis K. Mukherjee; Mojibur Rohman Khan (Food Bioscience, 2024)

Genetic exploration of variability and environmental influence on yield, components, and nutritional properties among groundnut germplasm originated from different countries for identification of potential stable donors - Kirti Rani; B. C. Ajay; Sandip Kumar Bera; Mahesh Kumar Mahatma; Sushmita Singh; K. Gangadhara; A. L. Rathnakumar; Praveen Kona; Narendra Kumar; G. A. Rajanna (Genetic Resources and Crop Evolution, 2024)

Bacterial communities and their predicted function change with the life stages of invasive C-strain Spodoptera frugiperda (J. E. Smith, 1797) (Lepidoptera: Noctuidae) - Sushmita Banra; Jaipal Singh Choudhary; Anand Kumar Thakur; Anita Kumari; Priti Kumari Oraon; Naiyar Naaz; Subhash Kumar Sahu; Kanika Kumari (Biological Invasions, 2024)

Potato in India: Its Growth, Trend and Export - Mrittika Das; Bankim Sarkar; P. K. Sahu; Ali Jamil Othman; Sushmita Ranjan (Potato Research, 2024)

Phylogenomic analysis of metagenome-assembled genomes indicates new taxa in the order Spirochaetales and proposal of Thalassospirochaeta sargassi gen. nov. sp. nov. from seaweeds - Kohli Pragya; Pannikurungottu Sreya; Lakshmanan Vighnesh; Dhurka Mahima; Mallick Sushmita; Chintalapati Sasikala; Chintalapati Venkata Ramana (Systematic and Applied Microbiology, 2024)

Microbial nitrogen transformations tracked by natural abundance isotope studies and microbiological methods: A review - Sushmita Deb; Dominika Lewicka-Szczebak; Lena Rohe (Science of The Total Environment, 2024)

Water deficit stress enhances the bioactive compounds of groundnut (Arachis hypogaea L.) kernels at the expense of primary metabolites - M.V. Solanki; M.K. Mahatma; Aman Varma; L.K. Thawait; Sushmita Singh; C.K. Jangir; M.D. Meena; R.S. Tomar; P.J. Rathod; Ashish Vala; U.K. Kandoliya (Food Bioscience, 2024)

Genome editing in peanuts: advancements, challenges and applications - Sushmita Singh; Chandramohan Sangh; Praveen Kona; Sandip Kumar Bera (The Nucleus, 2024)

Superposed transpressional tectonics of an intraterrane shear zone resulted in Shillong plateau evolution, NE India - Surajit Misra; Sushmita Bhattacharjee; Vashkar Jit Mahanta (Journal of Asian Earth Sciences, 2024)

AFB1 induced free radicals cause encephalopathy in goat kids via intrinsic pathway of apoptosis: pathological and immunohistochemical confirmation of non-hepatic neuroaflatoxicosis - Monalisa Sahoo; Jigarji Chaturji Thakor; Pradeep Kumar; Rajendra Singh; Pawan Kumar; Karampal Singh; Bhavani Puvvala; Ajay Kumar; Aswathy Gopinathan; Santwana Palai; Sushmita Patra; Jagannath Prasad Tripathy; et al. (Veterinary Research Communications, 2024)

microRNA-205 represses breast cancer metastasis by perturbing the rab coupling protein [RCP]-mediated integrin β1 recycling on the membrane - Saurav Bhattacharya; Sushmita Sarker; Shaswati Das; Manisha Ahir; Sreya Chattopadhyay; Swatilekha Ghosh; Arghya Adhikary (Apoptosis, 2024)

Elemental analysis of vertebrae discerns diadromous movements of threatened non‐marine elasmobranchs - Michael I. Grant; Peter M. Kyne; Julie James; Yi Hu; Sushmita Mukherji; Yolarnie Amepou; Leontine Baje; Andrew Chin; Grant Johnson; Tegan Lee; Brandon Mahan; Christopher Wurster; et al. (Journal of Fish Biology, 2023)
River sharks ( Glyphis spp.) and some sawfishes (Pristidae) inhabit riverine environments, although their long‐term habitat use patterns are poorly known. We investigated the diadromous movements of the northern river shark ( Glyphis garricki ), speartooth shark ( Glyphis glyphis ), narrow sawfish ( Anoxypristis cuspidata ), and largetooth sawfish ( Pristis pristis ) using in situ laser ablation inductively coupled plasma mass spectrometry (LA‐ICP‐MS) on vertebrae to recover elemental ratios over each individual's lifetime. We also measured elemental ratios for the bull shark ( Carcharhinus leucas ) and a range of inshore and offshore stenohaline marine species to assist in interpretation of results. Barium (Ba) was found to be an effective indicator of freshwater use, whereas lithium (Li) and strontium (Sr) were effective indicators of marine water use. The relationships between Ba and Li and Ba and Sr were negatively correlated, whereas the relationship between Li and Sr was positively correlated. Both river shark species had elemental signatures indicative of prolonged use of upper‐estuarine environments, whereas adults appear to mainly use lower‐estuarine environments rather than marine environments. Decreases in Li:Ba and Sr:Ba at the end of the prenatal growth zone of P. pristis samples indicated that parturition likely occurs in fresh water. There was limited evidence of prolonged riverine habitat use for A. cuspidata . The results of this study support elemental–environment relationships observed in teleost otoliths and indicate that in situ LA‐ICP‐MS elemental characterization is applicable to a wide range of elasmobranch species as a discriminator for use and movement across salinity gradients. A greater understanding of processes that lead to element incorporation in vertebrae, and relative concentrations in vertebrae with respect to the ambient environment, will improve the applicability of elemental analysis to understand movements across the life history of elasmobranchs into the future.

Synthesis, characterization, and phytotoxicity evaluation of Ce/Zr bimetallic oxides as adsorbents for nitrate decontamination from water - Neksumi Musa; Bharat Kumar Allam; Samreen Sajad; Nakshatra Bahadur Singh; Sushmita Banerjee (Groundwater for Sustainable Development, 2023)

Comprehensive bacterial-metabolite profiles of Hawaijar, Bekang, and Akhone: a comparative study on traditional fermented soybeans of north-east India - Sushmita Das; Maloyjo Joyraj Bhattacharjee; Ashis K. Mukherjee; Mojibur Rohman Khan (World Journal of Microbiology and Biotechnology, 2023)

Silica sources for arsenic mitigation in rice: machine learning-based predictive modeling and risk assessment - Rubina Khanam; Amaresh Kumar Nayak; Pedda Ghouse Peera Sheikh Kulsum; Jajati Mandal; Mohammad Shahid; Rahul Tripathy; Pratap Bhattacharyya; Panneer Selvam; Sushmita Munda; Sivashankari Manickam; Manish Debnath; Raghavendra Goud Bandaru (Environmental Science and Pollution Research, 2023)

Advancement in precision diagnosis and therapeutic for triple-negative breast cancer: Harnessing diagnostic potential of CRISPR-cas & engineered CAR T-cells mediated therapeutics - Vinayak Nayak; Sushmita Patra; Kshitij RB Singh; Bristy Ganguly; Das Nishant Kumar; Deepak Panda; Ganesh Kumar Maurya; Jay Singh; Sanatan Majhi; Rohit Sharma; Shyam S. Pandey; Ravindra Pratap Singh; et al. (Environmental Research, 2023)

Plant growth-promoting traits and activation of defense enzymes in traditional rice variety by fungal endophytes isolated from seeds of indigenous rice cultivars of Northeast India - Subham Roy; Anindita Sarma; Sushmita Paul; Dhurva Kumar Jha; Kumananda Tayung (South African Journal of Botany, 2023)

Failure of methanol detoxification in pests confers broad spectrum insect resistance in PME overexpressing transgenic cotton - Alka Srivastava; Gourav Jain; Sushmita; Sateesh Chandra; Vinay Kalia; Santosh Kumar Upadhyay; Rama Shanker Dubey; Praveen Chandra Verma (Plant Science, 2023)

Wild sesame (Sesamum prostratum Retz.) as potent source of salt tolerance through better physiological and biochemical adaptation than cultivated sesame (Sesamum indicum L.) - Mayank R. Raiyani; Anuj Kumar Singh; Kapil Kumar Tiwari; Hitendra S. Bhadauria; S. D. Solanki; Sushmita Singh (Vegetos, 2023)

Microfluidics engineering towards personalized oncology—a review - Sushmita Mishra; Murali Kumarasamy (In vitro models, 2023)

Investigation on water defluoridation via batch and continuous mode using Ce–Al bimetallic oxide: Adsorption dynamics, electrochemical and LCA analysis - Neksumi Musa; Bharat Kumar Allam; Nakshatra Bahadur Singh; Sushmita Banerjee (Environmental Pollution, 2023)

Ethrel-induced release of fresh seed dormancy causes remodelling of amylase activity, proteomics, phytohormone and fatty acid profile of groundnut (Arachis hypogaea L.) - Hemangini A. Chaudhari; Mahesh Kumar Mahatma; Virali Antala; Nidhi Radadiya; Piyush Ukani; Rukam Singh Tomar; Lokesh Kumar Thawait; Sushmita Singh; K. Gangadhara; Amar Sakure; Akrash Parihar (Physiology and Molecular Biology of Plants, 2023)

Author Correction to: A Refractory Case of Seborrheic Dermatitis Masquerading as Periorificial Dermatitis Successfully Treated by Oral Itraconazole - Sushmita Pradhan; Hui Xiao; Xin Ran; Daisuke Tsuruta; Hisayoshi Imanishi; Yuping Ran (Mycopathologia, 2023)

Accumulation of resveratrol, ferulic acid and iron in seeds confer iron deficiency chlorosis tolerance to a novel genetic stock of peanut (Arachis hypogaea L.) grown in calcareous soils - Sushmita Singh; Amrit Lal Singh; Kamal Krishna Pal; Kiran K. Reddy; K. Gangadhara; Rinku Dey; M. K. Mahatma; Aman Verma; Narendra Kumar; C. B. Patel; Lokesh Kumar Thawait; Suhail Ahmed; et al. (Physiology and Molecular Biology of Plants, 2023)

Slow negative feedback enhances robustness of square-wave bursting - Sushmita Rose John; Bernd Krauskopf; Hinke M. Osinga; Jonathan E. Rubin (Journal of Computational Neuroscience, 2023)
Square-wave bursting is an activity pattern common to a variety of neuronal and endocrine cell models that has been linked to central pattern generation for respiration and other physiological functions. Many of the reduced mathematical models that exhibit square-wave bursting yield transitions to an alternative pseudo-plateau bursting pattern with small parameter changes. This susceptibility to activity change could represent a problematic feature in settings where the release events triggered by spike production are necessary for function. In this work, we analyze how model bursting and other activity patterns vary with changes in a timescale associated with the conductance of a fast inward current. Specifically, using numerical simulations and dynamical systems methods, such as fast-slow decomposition and bifurcation and phase-plane analysis, we demonstrate and explain how the presence of a slow negative feedback associated with a gradual reduction of a fast inward current in these models helps to maintain the presence of spikes within the active phases of bursts. Therefore, although such a negative feedback is not necessary for burst production, we find that its presence generates a robustness that may be important for function.

A Refractory Case of Seborrheic Dermatitis Masquerading as Periorificial Dermatitis Successfully Treated by Oral Itraconazole - Sushmita Pradhan; Hui Xiao; Xin Ran; Daisuke Tsuruta; Hisayoshi Imanishi; Yuping Ran (Mycopathologia, 2023)

Dermoscopy Hints the Diagnosis of Candidal Granuloma Coinfected with Candida Parapsilosis and Candida Guilliermondii - Ying Huang; Sushmita Pradhan; Lina Li; Yuping Ran (Mycopathologia, 2023)

A retrospective study showing a high rate of seropositivity against SARS-CoV-2 in wild felines in India - Richa Borkakoti; M Karikalan; Sanket Kumar Nehul; Harsh Rajeshbhai Jogi; Kirtika Sharma; Sushmita Nautiyal; Ragini Mishra; Sonalika Mahajan; Sanchay Kumar Biswas; Sukdeb Nandi; Vishal Chander; Abhijit Pawde; et al. (Archives of Virology, 2023)

Characterization of Biomineralizing and Plant Growth-Promoting Attributes of Lithobiontic Bacteria - Kaushik Bhattacharjee; Sushmita Barua; Nikhil K. Chrungoo; Santa R. Joshi (Current Microbiology, 2023)

Study of elemental concentration, surface morphology and chemical characterization of atmospheric aerosols and trace gases in an urban environment (India) - Zainab Mushtaq; Pargin Bangotra; Sushmita Banerjee; Ansumali Ashish; Suman (Urban Climate, 2023)

Morpho-physiological and demographic responses of three threatened Ilex species to changing climate aligned with species distribution models in future climate scenarios - Prem Prakash Singh; Mukunda Dev Behera; Richa Rai; Uma Shankar; Krishna Upadhaya; Ibadahun Mary Nonghuloo; Aabid Hussain Mir; Sushmita Barua; Mariya Naseem; Pankaj Kumar Srivastava; Raghuvar Tiwary; Anita Gupta; et al. (Environmental Monitoring and Assessment, 2023)

Antiglycation activity of β- glucogallin from Asparagus racemosus - Shadab Ahmad; Alka Raj Pandey; Suriya Pratap Singh; Sushmita Singh; Koneni V. Sashidhara; Akhilesh K. Tamrakar (Natural Product Research, 2022)

Adaptations to high pressure of Nautilia sp. strain PV ‐1, a piezophilic Campylobacterium (aka Epsilonproteobacterium) isolated from a deep‐sea hydrothermal vent - Francesco Smedile; Dionysis I. Foustoukos; Sushmita Patwardhan; Kelli Mullane; Ian Schlegel; Michael W. Adams; Gerrit J. Schut; Donato Giovannelli; Costantino Vetriani (Environmental Microbiology, 2022)
Physiological and gene expression studies of deep‐sea bacteria under pressure conditions similar to those experienced in their natural habitat are critical for understanding growth kinetics and metabolic adaptations to in situ conditions. The Campylobacterium (aka Epsilonproteobacterium) Nautilia sp. strain PV‐1 was isolated from hydrothermal fluids released from an active deep‐sea hydrothermal vent at 9° N on the East Pacific Rise. Strain PV‐1 is a piezophilic, moderately thermophilic, chemolithoautotrophic anaerobe that conserves energy by coupling the oxidation of hydrogen to the reduction of nitrate or elemental sulfur. Using a high‐pressure–high temperature continuous culture system, we established that strain PV‐1 has the shortest generation time of all known piezophilic bacteria and we investigated its protein expression pattern in response to different hydrostatic pressure regimes. Proteogenomic analyses of strain PV‐1 grown at 20 and 5 MPa showed that pressure adaptation is not restricted to stress response or homeoviscous adaptation but extends to enzymes involved in central metabolic pathways. Protein synthesis, motility, transport, and energy metabolism are all affected by pressure, although to different extents. In strain PV‐1, low‐pressure conditions induce the synthesis of phage‐related proteins and an overexpression of enzymes involved in carbon fixation.

An overview of remote monitoring methods in biodiversity conservation - Rout George Kerry; Francis Jesmar Perez Montalbo; Rajeswari Das; Sushmita Patra; Gyana Prakash Mahapatra; Ganesh Kumar Maurya; Vinayak Nayak; Atala Bihari Jena; Kingsley Eghonghon Ukhurebor; Ram Chandra Jena; Sushanto Gouda; Sanatan Majhi; et al. (Environmental Science and Pollution Research, 2022)

Green synthesis of antimicrobial selenium and gold nanoparticles using Aegle marmelos fruit extract - Rajesh Dev Sarkar; Sushmita Mena; Amrit Kumar; Rantumoni Sharma; Namita Nath; Dhruva Kumar Jha; Mohan Chandra Kalita (Vegetos, 2022)

Reactive Oxygen Species in Modulating Intestinal Stem Cell Dynamics and Function - Arijit Nath; Pitam Chakrabarti; Sushmita Sen; Ananya Barui (Stem Cell Reviews and Reports, 2022)

Potentials of ketogenic diet against chronic kidney diseases: pharmacological insights and therapeutic prospects - Sushmita Kundu; Khandkar Shaharina Hossain; Akhi Moni; Md. Sarwar Zahan; Md. Masudur Rahman; Md Jamal Uddin (Molecular Biology Reports, 2022)

Symmetrical Sporotrichosis: Self-inoculated by Frequently Contacting Skin Lesion? - Lu Zheng; Xin Ran; Sushmita Pradhan; Yuping Ran (Mycopathologia, 2022)

Vehicular traffic noise modelling of urban area—a contouring and artificial neural network based approach - Abhijit Debnath; Prasoon Kumar Singh; Sushmita Banerjee (Environmental Science and Pollution Research, 2022)

Effect on mechanical properties of lightweight sustainable concrete with the use of waste coconut shell as replacement for coarse aggregate - Karthiga Shenbagam Natarajan; Dhivya Ramalingasekar; Sushmita Palanisamy; Mohanraj Ashokan (Environmental Science and Pollution Research, 2022)

Sonochemical synthesis of silica supported iron nanoparticles for enhanced removal of Cr(VI) species from aqueous medium - Neelam Shukla; Abhijit Debnath; Sushmita Banerjee (Nanotechnology for Environmental Engineering, 2022)

Impact of Land Use and Land Cover Change on Ecosystem Services in Eastern Coast of India - Rahul Tripathi; Khitish Chandra Moharana; Sangita Mohanty; Suchismita Pattnaik; Dibyendu Chatterjee; Chinmaya Kumar Swain; Anjani Kumar; Prafulla Kumar Nayak; Bipin Bihari Panda; Debarti Bhaduri; Sushmita Munda; Rubina Khanam; et al. (International Journal of Environmental Research, 2022)

Glucose-Induced Biofilm Formation in Bacillus thuringiensis KPWP1 is Associated with Increased Cell Surface Hydrophobicity and Increased Production of Exopolymeric Substances - Sushmita Jha; Nirbhay K. Bhadani; Abhinash Kumar; Tapas K. Sengupta (Current Microbiology, 2022)

Biochemical, molecular and in silico characterization of arsenate reductase from Bacillus thuringiensis KPWP1 tolerant to salt, arsenic and a wide range of pH - Paromita Banerjee; Ananya Chatterjee; Sushmita Jha; Nirbhay K. Bhadani; Partha P. Datta; Tapas K. Sengupta (Archives of Microbiology, 2022)

Insights into the physiological and molecular responses of plants to iron and zinc deficiency - Sushmita Singh; Amritlal Singh; Rinku Dey; Mahesh Mahatma; Kiran Reddy; Anuj Kumar Singh; K. Gangadhara; Sujit K. Bishi (Plant Physiology Reports, 2021)

Skin Microbiota in Non-inflammatory and Inflammatory Lesions of Acne Vulgaris: The Underlying Changes within the Pilosebaceous Unit - Xiaoxi Xu; Xin Ran; Jiaoqing Tang; Sushmita Pradhan; Yaling Dai; Kaiwen Zhuang; Yuping Ran (Mycopathologia, 2021)

CorGO: An Integrated Method for Clustering Functionally Similar Genes - Namrata Pant; Madhumita Madhumita; Sushmita Paul (Interdisciplinary Sciences: Computational Life Sciences, 2021)

Herbicide-Mediated Effects on Soil Microbes, Enzymes and Yield in Direct Sown Rice - Sunita Meher; Sanjoy Saha; Nitish Tiwari; P. Panneerselvam; Sushmita Munda; Ashirbachan Mahapatra; Hemant Kumar Jangde (Agricultural Research, 2021)

Preliminary age and growth estimates of the blue shark (Prionace glauca) from Papua New Guinea - Sushmita Mukherji; Jonathan Smart; Brooke D’Alberto; Leontine Baje; Andrew Chin; William White; Colin A. Simpfendorfer (Environmental Biology of Fishes, 2021)

Genetic and phylogenetic characterization of polycistronic dsRNA segment-10 of bluetongue virus isolates from India between 1985 and 2011 - Sanchay Kumar Biswas; Bimalendu Mondal; Karam Chand; Sushmita Nautiyal; Saravanan Subramaniam; Karam Pal Singh; Vivek Kumar Gupta; Muthannan Andavar Ramakrishnan (Virus Genes, 2021)

Asymmetric development of the Himalaya: quantitative evidence from strain analysis in Kimin-Ziro-Tamen area, Arunachal Lesser Himalaya, India - Gaurav Joshi; Amar Agarwal; K. K. Agarwal; P. V. Singh; Sushmita Singh (International Journal of Earth Sciences, 2021)

Role of Oncofetal Protein CR-1 as a Potential Tumor Marker for Oral Squamous Cell Carcinoma - Anu Jain; Sumanth Kumar Mallupattu; Reetu Thakur; Satyawati Mohindra; Amanjit Bal; Ashim Das; Sushmita Ghoshal; Arnab Pal (Indian Journal of Clinical Biochemistry, 2021)

Molecular characterization of porcine group A rotavirus to contain piglet diarrhea for productivity enhancement in North East India - Sushmita Das; Pranab Jyoti Das; Pratap Jyoti Handique (VirusDisease, 2021)

Genetic Diversity and Population Structure of a Medicinal Herb Houttuynia cordata Thunb. of North-East India - Sushmita Gupta; Raju Bharalee (Plant Molecular Biology Reporter, 2021)

Mitotic checkpoint defects: en route to cancer and drug resistance - Sinjini Sarkar; Pranab Kumar Sahoo; Sutapa Mahata; Ranita Pal; Dipanwita Ghosh; Tanuma Mistry; Sushmita Ghosh; Tanmoy Bera; Vilas D. Nasare (Chromosome Research, 2021)

Salicylic Acid and Hydrogen Peroxide Improve Antioxidant Response and Compatible Osmolytes in Wheat (Triticum aestivum L.) Under Water Deficit - Sushmita Singh; Pravin Prakash; Anuj Kumar Singh (Agricultural Research, 2021)

Exploration of Circulating Tumour Cell (CTC) Biology: A Paradigm Shift in Liquid Biopsy - Anshika Chauhan; Rajandeep Kaur; Sushmita Ghoshal; Arnab Pal (Indian Journal of Clinical Biochemistry, 2021)

Facial Sporotrichosis with Liver Cirrhosis Detected by Calcofluor White Treated with Itraconazole - Lina Li; Shoumin Zhang; Sushmita Pradhan; Yuping Ran (Mycopathologia, 2021)

Green silver nano-particles: synthesis using rice leaf extract, characterization, efficacy, and non-target effects - Totan Adak; Harekrushna Swain; Sushmita Munda; Arup Kumar Mukherjee; Manoj Kumar Yadav; Aravindan Sundaram; Manas Kumar Bag; Prakash Chandra Rath (Environmental Science and Pollution Research, 2021)

Monitoring Adventitious Presence of Transgenes in Cotton Collections from Genebank and Experimental Plots: Ensuring GM-Free Conservation and Cultivation of Genetic Resources - Monika Singh; Gurinderjit Randhawa; Rajesh K. Bhoge; Sushmita Singh; Anjali Kak; Omender Sangwan (Agricultural Research, 2020)

Molecular characterization and expressional quantification of lgp2 , a modulatory co‐receptor of RLR‐signalling pathway in the Indian major carp Labeo rohita following pathogenic challenges and PAMP stimulations - Arpita Mohanty; Sushmita Sadangi; Mahismita Paichha; Mrinal Samanta (Journal of Fish Biology, 2020)
Lgp2 (laboratory of genetics and physiology 2) is a cytosolic viral sensor of the RLR (retinoic acid‐inducible gene 1 like receptor) family member without the caspase recruitment domain, having both inhibitory and stimulatory roles in RLR‐signalling pathway. In India, Labeo rohita (rohu) is one of the leading and economically favoured freshwater fish species. Several immunological sentry proteins have been reported in this fish species, but no information is available on the RLR members. This study was aimed at cloning and characterization of full‐length lgp2 ‐cDNA (complementary DNA) in rohu and investigation of its expressional modulations following various pathogen‐associated molecular pattern stimulations and bacterial infections. The full‐length lgp2 ‐cDNA sequence obtained through rapid amplification of cDNA ends‐PCR consisted of 2299 nucleotides with an open reading frame of 2034 bp encoding 677 amino acids. In rohu‐Lgp2, four conserved domains – a DEAD/DEAH box helicase domain, Pfam type‐III restriction enzyme domain, helicase superfamily c‐terminal domain and RIG‐I C‐terminal regulatory domain – have been detected. Within these domains, several important functional motifs, such as ATP‐binding site, ATPase motif, RNA unwinding motif and RNA‐binding sites, have also been identified. In healthy rohu, lgp2 gene was abundantly expressed in gill, liver, kidney, spleen and blood. In response to both in vitro and in vivo treatments using double‐stranded RNA (poly I:C), lgp2 gene expression was significantly ( P Labeo rohita gill) cells. lgp2 gene expression significantly ( P γ ‐ d ‐glutamyl‐meso‐diaminopimelic acid and muramyl dipeptide. In vivo treatment using lipopolysaccharide and A eromonas hydrophila ‐derived RNA resulted in both up‐ and down‐regulation of lgp2 gene expression. Upon gram‐positive and gram‐negative bacterial infections, the expression of the lgp2 gene increased at different times in almost all the tested tissues. These integrated observations in rohu suggest that Lgp2 is an antiviral and antibacterial cytosolic receptor. Significance Statement Lgp2, a cytosolic viral sensor of retinoic acid‐inducible gene 1 like receptor family member, has been cloned in Labeo rohita . The complete sequence of rohu lgp2 ‐complementary DNA consisted of 2299 nucleotides with an open reading frame of 2034 bp encoding 677 amino acids. It consisted of a DExDc, RES‐III, HELICc, Pfam RIG‐I_C‐RD, ATP‐binding site, ATPase motif, RNA unwinding motif and RNA‐binding site. Upon bacterial infection, double‐stranded RNA and various pathogen‐associated molecular pattern stimulations, lgp2 gene expression significantly increased, indicating its role as an antiviral and antibacterial cytosolic receptor.

Comprehensive review of ASC structure and function in immune homeostasis and disease - Ishan Agrawal; Sushmita Jha (Molecular Biology Reports, 2020)

Molecular characterization and expression analysis of two crucial MAPKs‐ jnk1 and erk1 as cellular signal transducers in Labeo rohita in response to PAMPs stimulation and pathogenic invasion - Sushmita Sadangi; Arpita Mohanty; Mahismita Paichha; Mrinal Samanta (Journal of Fish Biology, 2020)
Mitogen‐activated protein kinases (MAPKs) are crucial Ser/Thr protein kinases that play important roles in innate immunity by converting extracellular stimuli into a wide range of cellular responses, including the production of cytokines. In this study, two MAPK genes, jnk1 and erk1 , were cloned and characterized in rohu ( Labeo rohita ), a commercially important freshwater fish species in the Indian subcontinent. In healthy rohu, both jnk1 and erk1 gene expressions were highest in the spleen as compared to gill, liver, blood and kidney tissues. In vitro stimulation of the L. rohita gill (LRG) cell line with γ‐D‐glutamyl‐meso‐diaminopimelic acid, muramyl dipeptide and polyinosinic: polycytidylic acid (poly I:C) resulted in significantly enhanced expressions of jnk1 and erk1 genes. In the in vivo experiments, jnk1 and erk1 gene expressions were also enhanced in lipopolysaccharides and poly I:C‐treatment. Infection of rohu fingerlings with Aeromonas hydrophila and Bacillus subtilis revealed significantly enhanced expressions of the jnk1 and erk1 genes in all of the tested organs/tissues. Together these results imply the important role of jnk1 and erk1 genes in fish during pathogenic invasion and diseases.

Deciphering the associated risk on soil microbes upon use of biopesticides in rice ecosystem - Tanushree Mishra; Guru-Pirasanna-Pandi Govindharaj; Basana Gowda Gadratagi; Naveenkumar B. Patil; Manoj Kumar Yadav; Sushmita Munda; Arup Kumar Mukherjee; Mayabini Jena; Totan Adak (Environmental Monitoring and Assessment, 2019)

Adipose tissue derived mesenchymal stem cells are better respondents to TGFβ1 for in vitro generation of cardiomyocyte-like cells - Anupama Kakkar; Sushmita Bose Nandy; Suchi Gupta; Balram Bharagava; Balram Airan; Sujata Mohanty (Molecular and Cellular Biochemistry, 2019)

Investigation on Microecology of Hair Root Fungi in Androgenetic Alopecia Patients - Jinghong Huang; Yuping Ran; Sushmita Pradhan; Wei Yan; Yaling Dai (Mycopathologia, 2019)

A high-density genetic map and molecular sex-typing assay for gerbils - Thomas D. Brekke; Sushmita Supriya; Megan G. Denver; Angharad Thom; Katherine A. Steele; John F. Mulley (Mammalian Genome, 2019)

Treatment of landfill leachate by integrated sequence of air stripping, coagulation–flocculation and adsorption - Sushmita De; Tumpa Hazra; Amit Dutta (Environment, Development and Sustainability, 2019)

Sustainable treatment of municipal landfill leachate by combined association of air stripping, Fenton oxidation, and enhanced coagulation - Sushmita De; Tumpa Hazra; Amit Dutta (Environmental Monitoring and Assessment, 2019)

Iron oxide labeling does not affect differentiation potential of human bone marrow mesenchymal stem cells exhibited by their differentiation into cardiac and neuronal cells - Sujata Mohanty; Krishan Gopal Jain; Sushmita Bose Nandy; Anupama Kakkar; Manoj Kumar; Amit Kumar Dinda; Harpal Singh; Alok Ray (Molecular and Cellular Biochemistry, 2018)

Occupational variation in the risk of female breast cancer in the Nordic countries - Sushmita Katuwal; Jan Ivar Martinsen; Kristina Kjaerheim; Pär Sparen; Laufey Tryggvadottir; Elsebeth Lynge; Elisabete Weiderpass; Eero Pukkala (Cancer Causes & Control, 2018)

Functional analysis of Salmonella Typhi adaptation to survival in water - Robert A. Kingsley; Gemma Langridge; Sarah E. Smith; Carine Makendi; Maria Fookes; Tom M. Wileman; Moataz Abd El Ghany; A. Keith Turner; Zoe A. Dyson; Sushmita Sridhar; Derek Pickard; Sally Kay; et al. (Environmental Microbiology, 2018)
Summary Contaminated water is a major risk factor associated with the transmission of Salmonella enterica serovar Typhi ( S. Typhi), the aetiological agent of human typhoid. However, little is known about how this pathogen adapts to living in the aqueous environment. We used transcriptome analysis (RNA‐seq) and transposon mutagenesis (TraDIS) to characterize these adaptive changes and identify multiple genes that contribute to survival. Over half of the genes in the S. Typhi genome altered expression level within the first 24 h following transfer from broth culture to water, although relatively few did so in the first 30 min. Genes linked to central metabolism, stress associated with arrested proton motive force and respiratory chain factors changed expression levels. Additionally, motility and chemotaxis genes increased expression, consistent with a scavenging lifestyle. The viaB‐associated gene tviC encoding a glcNAc epimerase that is required for Vi polysaccharide biosynthesis was, along with several other genes, shown to contribute to survival in water. Thus, we define regulatory adaptation operating in S. Typhi that facilitates survival in water.

NLRs as Helpline in the Brain: Mechanisms and Therapeutic Implications - Shalini Singh; Sushmita Jha (Molecular Neurobiology, 2018)

A putative NEM1 homologue regulates lipid droplet biogenesis via PAH1 in Tetrahymena thermophila - Sushmita Shukla; Anoop Narayana Pillai; Abdur Rahaman (Journal of Biosciences, 2018)

The influence of the carotid baroreflex on dynamic regulation of cerebral blood flow and cerebral tissue oxygenation in humans at rest and during exercise - Sushmita Purkayastha; Kaitlyn Maffuid; Xiaojie Zhu; Rong Zhang; Peter B. Raven (European Journal of Applied Physiology, 2018)

Proteomic and genomic responses of plants to nutritional stress - Rout George Kerry; Gyana Prakash Mahapatra; Sushmita Patra; Santi Lata Sahoo; Chinmay Pradhan; Bijaya Kumar Padhi; Jyoti Ranjan Rout (BioMetals, 2018)

Transgenic Tea Over-expressing Solanum tuberosum Endo-1,3-beta-d-glucanase Gene Conferred Resistance Against Blister Blight Disease - H. Ranjit Singh; Pranita Hazarika; Niraj Agarwala; Neelakshi Bhattacharyya; Prasenjit Bhagawati; Bornali Gohain; Tirthankar Bandyopadhyay; Raju Bharalee; Sushmita Gupta; Manab Deka; Sudripta Das (Plant Molecular Biology Reporter, 2018)

Small phosphatidate phosphatase (TtPAH2) of Tetrahymena complements respiratory function and not membrane biogenesis function of yeast PAH1 - Anoop Narayana Pillai; Sushmita Shukla; Sudhanshu Gautam; Abdur Rahaman (Journal of Biosciences, 2017)

Awareness of Undergraduate Dental and Medical Students Towards Oral Cancer - Ashish Shrestha; Vinay Marla; Sushmita Shrestha; Diksha Agrawal (Journal of Cancer Education, 2017)

Effect of Abiotic Factors on Degradation of Imidacloprid - Bibhab Mahapatra; Totan Adak; Naveen K. B. Patil; G. Guru P. Pandi; G. Basana Gowda; Manoj Kumar Yadav; S. D. Mohapatra; P. C. Rath; Sushmita Munda; Mayabini Jena (Bulletin of Environmental Contamination and Toxicology, 2017)

Modeling solubility of CO2/hydrocarbon gas in ionic liquid ([emim][FAP]) using Aspen Plus simulations - Bishwadeep Bagchi; Sushmita Sati; Vidyasagar Shilapuram (Environmental Science and Pollution Research, 2017)

Effect of Pretilachlor on Soil Enzyme Activities in Tropical Rice Soil - Subhashree Sahoo; Totan Adak; Torit B. Bagchi; Upendra Kumar; Sushmita Munda; Sanjoy Saha; J. Berliner; Mayabini Jena; B. B. Mishra (Bulletin of Environmental Contamination and Toxicology, 2017)

An Unusual Case of White Piedra Due to Trichosporon inkin Mimicking Trichobacteriosis - Kaiwen Zhuang; Xin Ran; Yaling Dai; Jiaoqing Tang; Qin Yang; Sushmita Pradhan; Yuping Ran (Mycopathologia, 2016)

Non-target effects of pretilachlor on microbial properties in tropical rice soil - Subhashree Sahoo; Totan Adak; Torit B. Bagchi; Upendra Kumar; Sushmita Munda; Sanjoy Saha; J. Berliner; Mayabini Jena; B. B. Mishra (Environmental Science and Pollution Research, 2016)

Effect of elevated CO2 on chlorpyriphos degradation and soil microbial activities in tropical rice soil - Totan Adak; Sushmita Munda; Upendra Kumar; J. Berliner; Somnath S. Pokhare; N. N. Jambhulkar; M. Jena (Environmental Monitoring and Assessment, 2016)

Molecular Landscape of Helopeltis theivora Induced Transcriptome and Defense Gene Expression in Tea - Tirthankar Bandyopadhyay; Bornali Gohain; Raju Bharalee; Sushmita Gupta; Priyadarshini Bhorali; Sourabh Kumar Das; Mohan C. Kalita; Sudripta Das (Plant Molecular Biology Reporter, 2015)

Cell Penetrating Peptides as Efficient Nanocarriers for Delivery of Antifungal Compound, Natamycin for the Treatment of Fungal Keratitis - Aastha Jain; Sushmita G. Shah; Archana Chugh (Pharmaceutical Research, 2015)

Erratum to: Morphological and microstructural evidences of paleo-seismic occurrences in an earthquake prone zone of Tripura, India - Sudip Dey; Sushmita Paul; Prasamita Sarkar (Journal of Earth Science, 2015)

Immune regulation of multiple sclerosis by CD8+ T cells - Sushmita Sinha; Farah R. Itani; Nitin J. Karandikar (Immunologic Research, 2014)

Morphological and microstructural evidences of paleo-seisminc occurrences in an earthquake prone zone of Tripura, India - Sudip Dey; Sushmita Paul; Prasamita Sarkar (Journal of Earth Science, 2014)

Informing future cartilage repair strategies: a comparative study of three different human cell types for cartilage tissue engineering - Sushmita Saha; Jennifer Kirkham; David Wood; Stephen Curran; Xuebin B. Yang (Cell and Tissue Research, 2013)

Studies on the removal of nickel from aqueous solutions using modified riverbed sand - Sandeep Yadav; Varsha Srivastava; Sushmita Banerjee; Fethiye Gode; Yogesh C. Sharma (Environmental Science and Pollution Research, 2013)

Metabolomics and protozoan parasites - Timothy Paget; Nicolas Haroune; Sushmita Bagchi; Edward Jarroll (Acta Parasitologica, 2013)
In this review, we examine the state-of-the-art technologies (gas and liquid chromatography, mass spectroscopy and nuclear magnetic resonance, etc.) in the well-established area of metabolomics especially as they relate to protozoan parasites.

SAVING TIME IN SPRINKLER IRRIGATION APPLICATION THROUGH CYCLIC OPERATION: A THEORETICAL APPROACH - Sushmita M. Dadhich; Rajesh Pratap Singh; P.S. Mahar (Irrigation and Drainage, 2012)
This paper describes a mathematical approach for time saving by using a variable application rate of water compared to a constant application rate in a sprinkler irrigation system. A mathematical equation was developed for a variable application rate based on the infiltration rate of soil and the water application rate of sprinklers. To apply a given depth of water, the time saving was calculated by on–off cycles of sprinklers through variable application rate over constant application rate of water. A commonly available sprinkler model was selected for this study. The time saving achieved using the variable application rate was calculated and compared to apply to a 10 cm depth of water. The maximum time saving was achieved at the highest operating pressures recommended by the manufacturer. Copyright © 2012 John Wiley & Sons, Ltd.

Identification of drought tolerant progenies in tea by gene expression analysis - Sushmita Gupta; Raju Bharalee; Priyadarshini Bhorali; Tirthankar Bandyopadhyay; Bornali Gohain; Niraj Agarwal; Parveen Ahmed; Hemanta Saikia; Sangeeta Borchetia; M. C. Kalita; A. K. Handique; Sudripta Das (Functional & Integrative Genomics, 2012)

Gilt required for RTL550-CYS-MOG to treat experimental autoimmune encephalomyelitis - Gregory G. Burrows; Roberto Meza-Romero; Jianya Huan; Sushmita Sinha; Jeffrey L. Mooney; Arthur A. Vandenbark; Halina Offner (Metabolic Brain Disease, 2012)

Geobacter: The Electric Microbe! Efficient Microbial Fuel Cells to Generate Clean, Cheap Electricity - Sushmita Poddar; Surbhi Khurana (Indian Journal of Microbiology, 2011)

Recombinant TCR Ligand Reverses Clinical Signs and CNS Damage of EAE Induced by Recombinant Human MOG - Sushmita Sinha; Sandhya Subramanian; Ashley Emerson-Webber; Maren Lindner; Gregory G. Burrows; Marjorie Grafe; Christopher Linington; Arthur A. Vandenbark; Claude C. A. Bernard; Halina Offner (Journal of Neuroimmune Pharmacology, 2010)

Insulin resistance due to lipid-induced signaling defects could be prevented by mahanine - Anindita Biswas; Sushmita Bhattacharya; Suman Dasgupta; Rakesh Kundu; Sib Sankar Roy; Bikas C. Pal; Samir Bhattacharya (Molecular and Cellular Biochemistry, 2010)

Volume and Shape in Feature Space on Adaptive FCM in MRI Segmentation - Renjie He; Balasrinivasa Rao Sajja; Sushmita Datta; Ponnada A. Narayana (Annals of Biomedical Engineering, 2008)

Investigation of the Drug Release and Surface Morphological Properties of Film-Coated Pellets, and Physical, Thermal and Mechanical Properties of Free Films as a Function of Various Curing Conditions - Sushmita Bhattacharjya; Dale Eric Wurster (AAPS PharmSciTech, 2008)

Effect of curing on water diffusivities in acrylate free films as measured via a sorption technique - Dale Eric Wurster; Sushmita Bhattacharjya; Douglas R. Flanagan (AAPS PharmSciTech, 2007)

Unified Approach for Multiple Sclerosis Lesion Segmentation on Brain MRI - Balasrinivasa Rao Sajja; Sushmita Datta; Renjie He; Meghana Mehta; Rakesh K. Gupta; Jerry S. Wolinsky; Ponnada A. Narayana (Annals of Biomedical Engineering, 2006)